Governance in the Twenty-first Century : revitalizing the public service (Series on governance and public management., 2000)
In Governance in the Twenty-first Century Canadian and international experts recognize both the difficulty of making predictions and the need to consider the future in order to prepare the public sector for new challenges. The authors' predictions and recommendations are anchored in a thorough understanding of contemporary public administration. They point out that not only have previous reforms made yet more change necessary and inevitable but that the purpose of these reforms is to attempt to return government to the position of respect and competence it enjoyed in the past. Contributors include Peter Aucoin (Dalhousie), Jonathan Boston (University of Wellington, New Zealand), Jacques Bourgault (École nationale d'administration publique Montréal), David R. Cameron (Toronto), Ralph Heintzman (Treasury Board Canada), Christopher Hood (London School of Economics and Political Science), Patricia W. Ingraham (The Maxwell School, Syracuse University), Donald P. Moynihan (The Maxwell School, Syracuse University), Jon Pierre (Göteborg University), B. Guy Peters, Christopher Pollitt (Erasmus University, The Netherlands), Donald J. Savoie, Richard Simeon (Toronto), Ignace Th.M. Snellen (Erasmus University, The Netherlands), and Vincent Wright (Oxford, England).